Lived experiences of ICT use in teaching and learning of history in one selected school of Chris Hani West District - Amahle Mbenyana; Owen Madalambana (Eureka: Journal of Educational Research, 2026)
The integration of Information and Communication Technology (ICT) is pivotal in modern education, enhancing teaching and enabling interactive, enquiry-based learning in History. Despite its benefits, integrating ICT in educational institutions remains challenging, particularly in schools located in rural and semi-urban areas. This qualitative study explored the lived experiences of teachers and learners in the use of ICT in the teaching and learning of History in one selected school within the Chris Hani West District in Eastern Cape Province of South Africa Guided by the Constructivist Learning Theory and the SAMR Model the research examined how ICT influences pedagogical practices, learner engagement, and classroom interaction. Thematic analysis of participants' experiences showed that although ICT enhances student participation, creativity, and inquiry, its use remains inconsistent due to challenges like time constraints, lack of training, and limited access to digital tools. Teachers who practiced collaborative and incremental ICT adoption seemed to develop a growing sense of confidence and pedagogical innovation. The study concludes that continuous professional development, supportive leadership, and context-sensitive implementation strategies are necessary for effective and sustainable integration of ICT. This study contributes to a very small, yet emerging, knowledge base on Technology-Integrated Education in History in under-resourced settings through a theoretically and practically grounded conception of the experiences within this sector. This study, theoretically and practically, offers a framework for incorporating ICT in a pedagogic and contextually appropriate manner within History Education in a South African setting.